Successful management of a common carotid artery injury using a Pruitt-F3 Carotid Shunt: a case report - Kang Kook Choi; Jayun Cho; Min A Lee; Soo Min Eun; Yang Bin Jeon (Journal of Trauma and Injury)
Penetrating neck injuries are a surgical challenge. In particular, penetrating neck injuries associated with carotid artery injuries have a high mortality rate. Overt external hemorrhage is unanimously considered as an indication for surgical exploration. The authors present a case of successful surgical management for a penetrating common carotid artery injury using a Pruitt-F3 Carotid Shunt (LeMaitre Vascular Inc., Burlington, MA, USA) in a 60-year-old male patient who was transferred to the level 1 trauma center due to a metal fragment piercing his neck while working. Active pulsatile bleeding was observed from the 3-cm-long external wound on the anterior neck in zone II. Emergent neck exploration showed near-total transection of the left common carotid artery just below the carotid bifurcation. After a Pruitt-F3 Carotid Shunt was applied to the injured carotid artery as a temporary vascular shunt, artificial graft interposition was performed for the injured common carotid artery. The patient experienced cerebral infarction as a complication caused by ischemia-reperfusion of the common carotid artery but was discharged in a suitable state for rehabilitation therapy.